Họ nguyên hàm của hàm số \(f(x)=x\mathrm{e}^{2x}\) là
\(F(x)=2\mathrm{e}^{2x}\left(x-\dfrac{1}{2}\right)+C\) | |
\(F(x)=2\mathrm{e}^{2x}(x-2)+C\) | |
\(F(x)=\dfrac{1}{2}\mathrm{e}^{2x}(x-2)+C\) | |
\(F(x)=\dfrac{1}{2}\mathrm{e}^{2x}\left(x-\dfrac{1}{2}\right)+C\) |
Chọn phương án D.
Đặt \(\begin{cases}
u=x\\ v'=\mathrm{e}^{2x}
\end{cases}\Rightarrow\begin{cases}
u'=1\\ v=\dfrac{1}{2}\mathrm{e}^{2x}
\end{cases}\)
Áp dụng phương pháp từng phần ta có $$\begin{aligned}
F(x)&=\dfrac{1}{2}x\mathrm{e}^{2x}-\displaystyle\int\dfrac{1}{2}\mathrm{e}^{2x}\mathrm{\,d}x\\
&=\dfrac{1}{2}x\mathrm{e}^{2x}-\dfrac{1}{4}\mathrm{e}^{2x}+C\\
&=\dfrac{1}{2}\mathrm{e}^{2x}\left(x-\dfrac{1}{2}\right)+C.
\end{aligned}$$